# Algebra help??? Thank you?

This is involving substitution

5x - 2y = -5

y - 5x = 3

Thank you, algebra is literally very hard for me, my text book is like reading greek and my instructor is no help at all.

Relevance

5x - 2y = -5

y - 5x = 3

1. Solve for one variable in terms of the other. I will solve for y since it's the simplest in the 2nd equation.

thus you get:

y = 3 + 5x

2. Next, plug in the value of the variable you solved for into the equation you did not use. In our case, I am plugging y = 3 + 5x into the first equation so I get,

5x - 2*(3+5x) = -5

3. Solve for the unknown variable

5x - 6 - 10x = -5

-5x - 6 = -5

-5x = 1

x = -1/5

4. Take the answer you found and plug it into the other equation. So you get

y - 5x = 3

y = 3 + 5x = 3 + (5*(-1/5)) = 2

thus: x = -1/5, y = 2

• Go to your school and see about a tutoring or after school program before you get to far behind. Now, the last time I did algebra it was in the 1960's but

here goes nothing

5x - 2y = -5 y -5x = 3

+2 y = +2y +5x = +5 x

5x = - 5 + 2y y = 3+ 5x

then 5x = - 5 + 2(3+ 5x)

5x = -5 +6 + 10 x

5x = 1 + 10 x

-10x = -10 x

- 5x = 1

x = -1/5

• well from y - 5x = 3 you get

y = 3 + 5x.

Now you have a y equals something. In the other equation you literally substitute every y you see with (3 + 5x). So,

5x - 2y = -5 then becomes 5x - 2*(3 + 5x) = -5.

Careful, you have to distribute the 2.

5x - 6 - 10x = -5

-5x = 1

x = -1/5

y = 3 + 5*-1/5

y = 3 -1 = 2 and you can check it by plugging in 2 for y and -1/5 for x in the original question:

5x - 2y = -5

5*(-1/5) - 2*2 = -5

-1 - 4 = -5

and so then you know the answers are correct.

• 1. Arrange y - 5x = 3 so that it is -5x + y = 3

2. Add both equations. (5x - 2y = -5)+ (-5x + y = 3) to cancel out the "x" term and find the "y" value first.

4. Find y by dividing both terms by -1. Answer is y = 2

5. Now that you have the number for the variable y, substitute the "y" in -5x + y = 3 with 2.

6. Solve, answer should be -5x + 2 = 3.

7. Subtract 2 from both sides to leave the -5x alone. Answer should be -5x = 1.

8. Divide both sides by -5 to get x alone. Answer should be x = -1/5.

9. Now that you have both the x and y terms, substitute it with the numbers (-1/5 and 2) in the equation 5x - 2y = -5.

10. By using the distributive property, you should have came up with -1 - 4 =-5.

11. -5 = -5, complete!

12. Your answer is correct because you have use simple mathematical operations to find the value of the variables. By substituting the number value of the variable in the equation and solving it, you are double checking to see if the number value you came up with for the variable is correct. So, the answer for this problem is y = 2, x = -1/5.

• First you take the second equation

y-5x = 3

hence y= 3+5x

Substituting for y in the first equation, we get

5x-2y= -5

or that is 5x - 2(3+5x) = -5

or that is 5x - 6 - 10x = -5

or that is -5x - 6 = -5

or that is -5x = -5+6 = 1

therefore x = 1/-5 = - 1/5

substitute the value of x into the second equation to find the value of y

that is y - 5(-1/5) = 3

or that is y +1 = 3

hence y = 3 - 1 = 2

verify your answer by putting the values of x and y into the second equation

that is

y-5x = 3

equals to 2 - 5 (-1/5) = 3

equals to 2 +1 = 3

equals to 3 = 3

LHS = RHS

Hence the values of x and y calculated are correct

• Take the second formula and write it in Y= format. You'll get:

y=5x+3

Now take this and place it in first. You get:

5x-2(5x+3)=-5

Solving this, you get:

5x-10x-6=-5

5x-10x=-5+6

-5x=1

x=-1/5

Now, place this into the second formula

y-5(-1/5)=3

solving this...

y+1=3

y=3-1

y=2

So you get: x=-1/5, y=2

You need to plug those into to both formula and make sure they are correct.

• X=1/15 by substitution

• y= 3+5x

5x- 2(3+5x)=-5

5x -6 -10x=-5

-5x=1

x= -1/5

y= 2

• y-5x=3

y=5x+3

5x-2(5x+3)=-5

5x-10x-6=-5

-5x=1

x=-1/5

y-5(-1/5)=3

y+1=3

y=2

thus,

x=-1/5, y=2

• Don't worry.It is very easy for me. and I can teach you ^^

Step 1

y=3+5x

Step 2

5x-2(3+5x)=-5

5x-6-10x=-5

-5x=1

x= - 1/5

Step 3

y=3+5x

y=3+(-1)

y=2

**************************************************